Additional file 6 of Development and validation of a novel predictive model for dementia risk in middle-aged and elderly depression individuals: a large and longitudinal machine learning cohort study - Xuan Xiao (117712) (2025)
Supplementary Material 6: eFigure 5 Hazard ratios of included variables for dementia risk prediction model. The point estimate of the Cox proportional hazards model’s hazard ratio is depicted by the centre of the Forest plot, and the two-sided 95% confidence intervals are indicated by the error bars, the vertical line is the line of no effect